Koefisien Difusi Ion Fosfat dalam Gel Asam Sitrat-Agarosa yang Digunakan dalam Gradien Difusif pada Sampler Pasif Film Tipis (DGT) - Digwanggi Arum Tazkiyatu An-Nufuus; Barlah Rumhayati; Qonitah Fardiyah; Diah Mardiana; Ulfa Andayani; Layta Dinira (Postgraduate, University of Mataram, 2023)
In this research, the diffusion coefficient of phosphate ions in agarose-citric acid diffusive gel has been studied. The agarose-citric acid diffusion layer was prepared by mixing 1.5% agarose solution with the addition of citric acid solutions at various concentration. The diffusive gel was casted between two glass plates which were separated using a spacer of 0.1 cm thickness and clamped together in the three sides. Gel was formed for 15 minutes in an oven at 40oC. The diffusion coefficient then was calculated using Fick's First law formula. Gel that produced with addition of 0.45% citric acid absorbed more water during immersion in water for 3 hours for facilitating phosphate diffusion. Swelling degree of the agarose citric acid diffusive gels was not affected by the storing solution condition either in water or in NaNO3 0.1 M. Coefficient diffusion of phosphate in the agarose-citric acid diffusive gel was 1.009Ã—10-7 cm2s-1, less than the diffusion in the pure agarose gel 1.367Ã—10-7 cm2s-1. The diffusion is affected by the ionic strength of solution. Phosphate diffusion coefficient is higher in the phosphate solution with addition of 2 mgL-1 nitrate. Increasing the ionic strength causes lower phosphate diffusion coefficient because the electrostatic attractive and repulsive force